Notes on the species of Abrostola Ochsenheimer, 1816 (Lepidoptera, Noctuidae, Plusiinae) from China, with the description of a new species - Hu, Yan-Qing; Yu, Yong; Huang, Zhen-Fu (Zootaxa, 2021)
This paper deals with seven species of Abrostola from China, among which one is new to science. The new species, Abrostola wanglangensis sp. nov., resembles Abrostola korbi Dufay, 1958 (known from Russia) and Abrostola pacifica Dufay, 1960 (known from Russia, Korean Peninsula and Japan). Adults and genitalia are illustrated.